SLAP IV IN OVERHEAD SPORTS PRACTICE - Patriota, Gyoguevara Sol Queiroz Andrade (Acta Ortop Bras, 2019)
Superior labral tear from anterior to posterior (SLAP) is the most common disease in overhead sports practice. OBJECTIVE: to evaluate the functional outcome after tenodesis of long head biceps tendon (LHBT) in high-performance patients with isolated SLAP lesion refractory to conservative treatment. METHODS: Patients underwent the same open repair procedure, using an interference screw. RESULTS: Both patients presented good clinical results and returned to the sport with performance similar to that prior to the injury. CONCLUSION: The results favor the surgical treatment of these athletes with SLAP IV. Level of Evidence IV, Série de Casos.